Implications of rural settlement patterns for development: case study in central and eastern economic region of Mongolia - Khishigdorj, Davaakhuu; Tseyenkhand, Punsantsogvoo (Proceedings of the Mongolian Academy of Sciences, 2019)
Under the three law of magnetism [1] the mechanism of pull-push is rapidly increasing [2] in the process of urbanization and as a result the role and function of some settlements have changed. The increase in the population of big cities affects the increase in the radius of influence of the settlement to surrounding area [3, 4]. One of the reasons of rural to urban migration among pastoral herder is growing interest in and attraction to intensive farming systems [4]. Therefore, there is an urgent need to identify proper population planning of settlements. This research work was carried out in 9 aimags: central and eastern economic regions of Mongolia. The population of small settlements has decreased under the influence of bigger settlements with market and better infrastructure. The roles of these little settlements are now changing to become centers for agricultural production as well as to provide new opportunities to migrant herders. Nevertheless, many of them still lack access to social services and infrastructure. Prior to the 1990s, much attention was given to urban development ensuring their uniformity, and each urban settlement had its own light and heavy industry. However, after the democratic transformations in 1990, agglomeration was carried out in a few settlements to attract population, while some other settlements were overseen. Therefore, it is important to specialize industrial enterprises at settlements, and improve their structure and create a multi-centered system.